A rare intronic mutation in the splice acceptor site of the CYP17A1 gene in a patient with 17α-hydroxylase/17, 20-lyase deficiency. (2nd January 2021) - Guo, Xudong; Wang, Hanbo; Xiang, Yuzhu; Ren, Xiangbin; Jiang, Shaobo
Abstract: Mutations of the CYP17A1 gene could cause complete or partial and combined or isolated 17α-hydroxylase/17, 20-lyase deficiency (17OHD), which is characterized by hypertension, hypokalemia, and abnormal development of the genitalia. Most of the mutations are located in the coding sequence, and very few are located in the intronic region. The aim of this study is to investigate the novel intronic CYP17A1 mutation and its possible influence on phenotype. A 30yearold Chinese female patient (46, XY) was referred to our Urology Department for severe hypertension, hypokalemia and a right adrenal mass. Physical examination revealed a hypertrophic clitoris and blind-ending vagina. Hormone analysis exhibited increased concentrations of ACTH and low levels of cortisol and sexual steroids. Mutation analysis revealed compound heterozygous CYP17A1 mutations, with c.1072C > T (p.Arg358*) in one allele and a novel intronic splicing mutation (c.970-1G > A) in another allele. Bioinformatics software predicted that the novel mutation may activate a cryptic splice site, shifting the reading frame and introducing a premature stop codon. In conclusion, we discovered a novel splicing mutation of the CYP17A1 gene in a Chinese patient with 17OHD. Our study extended the CYP17A1 mutation spectrum and provided valuable information for patient management and genetic counseling.